Sequential Nucleation Growth of ZnO Nanoflowers - Nora Elizondo; Dora Irma Martínez; Ana Maria Arato; Rodrigo González; Francisco Vázquez; Gustavo Rodríguez; Ernesto Torres; Víctor Manuel Castaño (Nano Biomedicine and Engineering, 2018)
The morphological characteristics of ZnO nanostructures were systematically studied from dense rods to flower-like shapes. The ZnO flower-like samples were prepared by direct decomposition of a Zn(OH)42– precursor and by the sequential nucleation and growth method consisted of a multistep synthesis of complex nanostructured films. Condition-dependent experiments systematically were compared as to reveal the formation and detailed growth process of ZnO nanosized crystallites and aggregates. X-ray diffraction, transmission and scanning electron microscopy indicated that the precursor, solution basicity, reaction temperature and pressure as well as reaction time, were responsible for the variations of the morphologies. ZnO flower-like and large nanorods of exceptional uniformity, orientation alignment, and optical properties have been produced in this work. Several synthesis steps are needed to produce oriented nanostructures that are more complex than simple nanorod architectures. These structures have potential applications in building functional electronics devices and optoelectronic properties.